Prognostic value of coronary flow velocity reserve in patients with homozygous familial hypercholesterolemia. Issue 9 (26th August 2021) - Xie, Jinjie; Yang, Ya; Wang, Luya; Pan, Yufan; Zhang, Ruiying; Qu, Yichen; Li, Rongjuan; Wen, Wenhui; Wu, Yue; Li, Jialu; Ma, Xiaohai
Abstract: Background: Coronary flow velocity reserve (CFVR) can provide useful quantitative information on the functional status of coronary artery circulation, and an impaired CFVR (< 2.0) was associated with a significant increase in the occurrence of cardiac events. Coronary artery disease (CAD) is the leading cause of death in homozygous familial hypercholesterolemia (HoFH), but the relationship between impaired CFVR and outcome in HoFH has never been discussed before Methods: To explore the long‐term prognostic value of CFVR in patients with HoFH, 39 HoFH patients with CFVR data (mean age with 16.7 years) were enrolled from the Genetic and Imaging of Familial Hypercholesterolemia in Han Nationality Study. All patients were divided into impaired CFVR (CFVR < 2.0, n = 17) and preserved CFVR (CFVR≥2.0, n = 22) group. Follow‐up was performed until a major adverse cardiac event (MACE) occurred or up to June 30, 2020 Results: During a median follow‐up of 89 months, 16 events were registered, 12 of which were occurred in the impaired CFVR group and four occurred in the preserved CFVR group. The event‐free survival rate of impaired CFVR group was significantly lower than that in the preserved CFVR group (29.4% vs 81.8%, P  < .001), and CFVR < 2.0 was independently associated with prognosis before and after adjustment for related risk factors (HR 5.197, 95% CI 1.669 to 16.178, P  = .004 and HR 5.488, 95% CI 1.470 to 20.496, P  = .011, respectively) Conclusions: an impaired CFVR predicts a worse outcome in HoFH. CFVR shows an independent value in the prediction of long‐term outcome in HoFH.